Model Project Based Learnıng Dengan Medıa Dıorama Mengoptımalkan Keterampılan Berbıcara Dan Menulıs Karangan Narası Sıswa Kelas V - Putra; Rusnilawati (Elementary Teacher Education Program, Majalengka University, 2023)
Teaching writing is something that is always taught in elementary schools. Even though almost all Indonesian language learning activities include writing, students' writing skills are still quite low. The level of proficiency in writing narrative essays is still quite low because students feel they lack writing talent and have difficulty translating their thoughts into clear and effective writing. This research aims to find out whether the Project Based Learning model with diorama media can optimize the speaking and narrative writing skills of class V students. This research is a quantitative research with a Pretest–Posttest Control Groupi Design research design. The population of this study was all fifth grade elementary school students in Gugus Melati. The sample was determined using a random sampling technique and class V of SDN Kaloran was determined as the experimental class, and class V of SDN 2 Sendang as the control class with a total of 20 students each. Data collection methods are carried out by means of observation, written tests, and documents. The data analysis techniques used were normality test, homogeneity test, paired sample t-test, independent t test, and anova test. The results of the research obtained an Fcount value of 4.694 with a significance value of 0.037<0.05 and Ha was accepted. So it can be concluded that the Project Based Learning Model with diorama media optimizes the speaking and narrative writing skills of class V students.